Assessment of heavy metal concentrations in commercially Farmed Fishes in the South‒West region of Bangladesh and associated health risk assessment (Bangladesh Journal of Scientific and Industrial Research, 2025)
Due to the different hazardous effects of heavy metals on human health, this study investigated the concentrations of the heavy metals lead (Pb) and chromium (Cr) in different commercially farmed fishes cultivated in Bangladesh and in their respective fish feeds (poultry stool from integrated farming or commercial fish feeds) to determine the sources of the contaminants and their associated health risks. Thirty fish samples were collected from ten different farms in three districts (Gopalganj, Madaripur, and Khulna) of Bangladesh. Farms from Gopalganj and Madaripur utilized poultry stool as the sole source of food, whereas commercially available fish feeds were used in Khulna. The concentrations of Pb and Cr in the fish and their respective diets were measured via an atomic absorption spectrophotometer. Although the Pb concentration exceeded the safe concentration in 53% of the fishes, the Cr concentration did not surpass in any of the fish samples. The Pb and Cr concentrations in the fish samples correlated with those in their respective fish feeds, suggesting bioaccumulation of these heavy metals through their diet. Although health risk analyses of the mean Pb and Cr concentrations in fish muscles revealed no noncarcinogenic (THQ and HI) risk, the carcinogenic risk associated with Cr was unacceptable in all three districts. The Pb and Cr concentrations in poultry stool samples were not significantly greater than those in commercial feed samples, indicating that, from a heavy metal perspective, there are no additional health risks associated with integrated farming compared with the usage of commercial fish feeds.Bangladesh J. Sci. Ind. Res. 60(1), 53-62, 2025